The learners’ conceptual understanding: Literature review of vapor-pressure lowering and boiling-point elevation - Rizki Nur Analita; Iriani Bakti; Putranty Widha Nugraheni; Ester Noviyanti (Journal of Education and Learning (EduLearn), 2023)
The learners’ conceptual understanding has become one of the leading research areas conducted by educational researchers. Both students and current educators should actively work to improve their understanding of alternative conceptions and deepen their conceptual knowledge. One of the essential concepts in chemistry learning is colligative properties. This research is a literature review that discusses vapor-pressure lowering and boiling-point elevation, parts of colligative properties concept. The method used a meta-analysis review that combined the results of multiple studies that required a systematic approach to research of the literature. A preferred reporting items for systematic reviews and meta-analysis or known as PRISMA process was used for study selection. The following literature review was summarized based on various studies from Indonesia, United States of America (USA), Turkey, and Greece. The aims of this review were to provide important details from several previous studies to help researchers obtain complete sources. The findings were also expected to provide the learner with the correct understanding of chemistry, especially in vapor-pressure lowering and boiling-point elevation concepts.